Bed Filtration Of Colloidal Particles (1838-Transactions Vol. 276) - T. A. Ring (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
The bed filtration of colloidal particles has been modeled by performing a differential particle balance. The balance considered the localized particle deposition rate to be the sum of three rate resistances: mass transfer to a region near the surface, adhesion onto a partially filled surface, and resuspension from a partially filled surface. The differential particle balance equations, one for the free particles and one for the adhered particles, were solved by a finite difference algorithm. Results of this model are compared to experimental filter breakthrough curves.